Anaphylactic shock following castor bean contact: a case report. Issue 1 (December 2017) - Coattrenec, Y.; Jaques, D.; Jandus, P.; Harr, T.; Spoerl, D.
Abstract Background The castor bean plant, Ricinus communis, is known to have allergenic and toxic properties. Castor bean allergy has been described mainly as an occupational inhalation allergy in laboratory workers, in persons working in oil processing mills or in agricultural industry. So far, only one case of anaphylactic reaction due to castor bean sensitization confirmed by specific IgE has been described in literature. Case presentation A 30-year-old woman presented to the emergency room with severe angioedema followed by urticaria, hypotension and tachycardia. She recovered after treatment with antihistamines, corticosteroids, nebulized adrenaline and intravenous fluids. Food induced anaphylaxis was excluded by allergological investigations. After repeated thorough history, the patient mentioned having bitten into a castor bean just before the reaction. Cutaneous test (prick-to-prick) and specific IgE for castor bean were highly positive. Conclusions We report the second case of a severe anaphylactic reaction to castor beans, confirmed by IgE testing, reported in the literature. It underlines the importance of a meticulous history in allergology and highlights the fact, that castor beans may cause potentially fatal anaphylaxis.